Silent Sinus Syndrome: An Acquired Condition - Hourany, Roula; Aygun, Nafi; Santina, Charley C. Della; Zinreich, S. James (American Journal of Neuroradiology, 2005)
Summary: We present the case of a 30-year-old man with silent sinus syndrome. A CT scan obtained 10 years earlier showed completely normal maxillary sinuses. This case illustrates the acquired nature of this disorder.